Patients with advanced pancreatic cancer treated with mistletoe and hyperthermia in addition to palliative chemotherapy: a retrospective single-center analysis - Hohneck, Anna; Sadikaj, Largsi; Heinemann, Lara; Schroeder, Maik; Riess, Hartmut; Gerhards, Annette; Burkholder, Iris; Heckel-Reusser, Stefan; Gottfried, Julia; Hofheinz, Ralf-Dieter (Cancers, 2023)
This retrospective analysis investigated the influence of integrative therapies in addition to palliative chemotherapy in patients with advanced pancreatic cancer, treated at a single institution specialized in integrative oncology between January 2015 and December 2019. In total, 206 consecutive patients were included in the study, whereof 142 patients (68.9%) received palliative chemotherapy (gemcitabine/nab-paclitaxel 33.8%; FOLFIRINOX 35.9%; gemcitabine 30.3%) while the remainder were treated with best supportive and integrative care. Integrative therapies were used in 117 of 142 patients (82.4%) in addition to conventional chemotherapy, whereby mistletoe was used in 117 patients (82.4%) and hyperthermia in 74 patients (52.1%). A total of 107/142 patients (86.3%) died during the observation period, whereby survival times differed significantly depending on the additional use of integrative mistletoe or hyperthermia: chemotherapy alone 8.6 months (95% CI 4.7-15.4), chemotherapy and only mistletoe therapy 11.2 months (95% CI 7.1-14.2), or a combination of chemotherapy with mistletoe and hyperthermia 18.9 months (95% CI 15.2-24.5). While the survival times observed for patients with advanced pancreatic cancer receiving chemotherapy alone are consistent with pivotal phase-III studies and German registry data, we found significantly improved survival using additional mistletoe and/or hyperthermia.
Gesehen am 22.07.2024